(untitled) (Journal of Atomic and Molecular Sciences, 2013)
The Frantz–Nodvik model was extended to propagate pulse through a double-pass laser amplifier and to study beam-interaction effects on the output-energy fluence and gain factor according to the distance between two beams. We also obtained the necessary approximation equations for the saturation state and small input pulse. The results show that minimum output energy and gain occur when two beams completely coincide. The comparison between numerical, analytical, and empirical results demonstrates a good correspondence.